Microtubule-associated protein 1A/1B-light chain 3 (LC3) ‘decorates’ intracytoplasmic inclusions in a patient with chronic lymphocytic leukaemia - Bussi, Claudio (2017)
A 77-year-old woman, diagnosed nine years previously with chronic lymphocytic leukaemia (CLL) Rai stage I, was referred to our hospital with disease progression (night sweats, weight loss and organomegaly). Her peripheral blood count showed leucocytosis (WBC 104 9 9 109 /l; 94% lymphocytes), anaemia (haemoglobin concentration 105 g/l) and a normal platelet count (146 9 109 /l). The monoclonal B-cell immunophenotype had been determined previously as lambda light chain-restricted, CD19+ , CD20dim, CD5+ , CD200+ , CD22dim, CD79bdim, surface membrane immunoglobulin (sIg)Mdim, CD23, CD10 and FMC7. A May-Grunwald-Giemsa-stained blood film showed € mature lymphocytes with around 50% of the total lymphocytes containing intracytoplasmic inclusions, seen as rectangular crystalline structures (top). The patient was treated with chlorambucil (unfit patient), several times, obtaining partial remission.